Twin Rectal Tonsils Mimicking Carcinoid or Mucosa-Associated Lymphoid Tissue Lymphoma - Masanori Takehara; Naoki Muguruma; Shinji Kitamura; Tetsuo Kimura; Koichi Okamoto; Hiroshi Miyamoto; Yoshimi Bando; Tetsuji Takayama (Korean Society of Gastrointestinal Endoscopy, 2017)
The rectal tonsil is a rare polypoid lesion exclusively found in the rectum and is considered a reactive proliferation of the lymphoid tissue. Although this lesion is benign, we recommend that it should be differentiated from carcinoid or polypoid type of mucosa-associated lymphoid tissue lymphomas, based on gross findings. In this case report, we describe a case of rectal lesions with a unique appearance in a 41-year-old man. Colonoscopy revealed two 5-mm-sized nodules located opposite from each other on the left and right sides of the lower rectum. Endoscopic mucosal resection was conducted. Histopathologically, both lesions were mainly located in the submucosa and consisted of prominent lymphoid follicles with germinal centers of various sizes. No immunoreactivity of Bcl-2 was seen in the germinal centers. Immunohistochemical staining for kappa and lambda light chains revealed a polyclonal pattern. Therefore, these lesions were diagnosed as rectal tonsils.